Responsible innovation in neurotechnology enterprises - Garden, Hermann (OECD Science, Technology and Industry Working Papers, 2019)
Novel neurotechnology offers significant potential for the promotion of health and economic growth. Spearheaded by large national and international flagship initiatives in brain science and fuelled by a clear medical need, research both in the public and private sector has made considerable strides towards novel neurotechnology, services and markets. At the same time, neurotechnology raises a range of unique ethical, legal, and policy questions that potential business models will have to address. This document is the result of analytical work on the opportunities and challenges of implementing responsibility frameworks into neurotechnology translation at major brain research initiatives and in the private sector. The report draws on: (1) the discussion at the BNCT workshop "Minding Neurotechnology: delivering responsible innovation for health and well-being", 2018, Shanghai, People's Republic of China; and (2) commentaries by workshop participants. The Workshop provided a forum for innovators to discuss strategies for delivering responsible innovation in neurotechnology